VHL-Mediated Regulation of CHCHD4 and Mitochondrial Function - Briston, Thomas; Stephen, Jenna M.; Thomas, Luke W.; Esposito, Cinzia; Chung, Yuen-Li; Syafruddin, Saiful E.; Turmaine, Mark; Maddalena, Lucas A.; Greef, Basma; Szabadkai, Gyorgy; Maxwell, Patrick H.; Vanharanta, Sakari; et al. (Frontiers in Oncology, 2018)
Dysregulated mitochondrial function is associated with the pathology of a wide range of diseases including renal disease and cancer. Thus, investigating regulators of mitochondrial function is of particular interest. Previous work has shown that the von Hippel-Lindau tumor suppressor protein (pVHL) regulates mitochondrial biogenesis and respiratory chain function. pVHL is best known as an E3-ubiquitin ligase for the α-subunit of the hypoxia inducible factor (HIF) family of dimeric transcription factors. In normoxia, pVHL recognizes and binds hydroxylated HIF-α (HIF-1α and HIF-2α), targeting it for ubiquitination and proteasomal degradation. In this way, HIF transcriptional activity is tightly controlled at the level of HIF-α protein stability. At least 80% of clear cell renal carcinomas exhibit inactivation of the VHL gene, which leads to HIF-α protein stabilization and constitutive HIF activation. Constitutive HIF activation in renal carcinoma drives tumor progression and metastasis. Reconstitution of wild-type VHL protein (pVHL) in pVHL-defective renal carcinoma cells not only suppresses HIF activation and tumor growth, but also enhances mitochondrial respiratory chain function via mechanisms that are not fully elucidated. Here, we show that pVHL regulates mitochondrial function when re-expressed in pVHL-defective 786O and RCC10 renal carcinoma cells distinct from its regulation of HIF-α. Expression of CHCHD4, a key component of the disulphide relay system (DRS) involved in mitochondrial protein import within the intermembrane space (IMS) was elevated by pVHL re-expression alongside enhanced expression of respiratory chain subunits of complex I (NDUFB10) and complex IV (mtCO-2 and COX IV). These changes correlated with increased oxygen consumption rate (OCR) and dynamic changes in glucose and glutamine metabolism. Knockdown of HIF-2α also led to increased OCR, and elevated expression of CHCHD4, NDUFB10 and COXIV in 786O cells. Expression of pVHL mutant proteins (R200W, N78S, D126N and S183L) that constitutively stabilize HIF-α but differentially promote glycolytic metabolism, were also found to differentially promote the pVHL-mediated mitochondrial phenotype. Parallel changes in mitochondrial morphology and the mitochondrial network were observed. Our study reveals a new role for pVHL in regulating CHCHD4 and mitochondrial function in renal carcinoma cells.